SELF-EDUCATION THROUGH MOBILE APPLICATIONS - Djurayev Iqbol Ilyosovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In the article we research that Intelligent mobile applications has brought tremendous changes to mobile learning. Open multimedia learning resources are a powerful supplement to traditional printed books. Differentiated teaching materials also give students many choices and stimulate their enthusiasm for learning; rich and easy-to-use online teaching resources have a great influence on traditional teaching resources. Knowledgeable people are no longer the only teachers, and students can follow and choose what they need to learn flexibly according to their needs and weaknesses. Using app to assist learning, teaching can improve learning effects and stimulate students’ interest in learning. With the popularity and the continuous development of mobile learning applications, applications have become an important part of our daily lives.